ПОМИНАЛЬНО-ПОГРЕБАЛЬНЫЕ ОБРЯДЫ НЕКРОПОЛЯ ОЛЬВИИ, СВЯЗАННЫЕ С КУЛЬТОМ ХТОНИЧЕСКИХ БОГОВ И ГЕРОЕВ (Zaporizhzhia Historical Review, 2021)
The article deals with the connection between burial rite of the Olbio Necropolis and the cult of a horse and a dog in the antique mythology. The horse and the dog represented both life and death totems. Graves with representation of horses were excavated in the Olbio Necropolis and in a number of other antique towns. Besides, the remains of horses and dogs were excavated in some burial places. The Necropolis was the place where horses and dogs were sacrificed to honour Chtonic gods.